Behavioral, Reproductive, and Environmental Factors Associated with Infertility Among Reproductive-Age Couples - I Gusti Ayu Ratih Agustini (Asosiasi Dosen Muda Indonesia, 2026)
Infertility is a reproductive health problem that can affect the biological, psychological, social, and economic well-being of couples. Its occurrence may be associated with various behavioral, reproductive, and environmental factors, requiring a comprehensive assessment involving both partners. Objective: This study aimed to analyze factors associated with infertility among couples of reproductive age in Denpasar, Bali. The study specifically examined smoking, alcohol consumption, reproductive disease history, and risky environmental exposure as potential factors associated with infertility. Methodology: This quantitative observational analytic study employed a case-control design involving 100 participants, consisting of 50 participants in the infertility group and 50 participants in the control group. Primary data were collected using a structured questionnaire, while secondary data were obtained from medical records and reproductive health service documentation. Data were analyzed using descriptive statistics and bivariate analysis. The strength of each association was reported using crude odds ratios, 95% confidence intervals, and p-values. Findings: Smoking was significantly associated with infertility (OR = 4.70; 95% CI: 1.93–11.42; p < 0.001). Alcohol consumption was associated with higher odds of infertility (OR = 8.43; 95% CI: 1.79–39.70; p = 0.002). A history of reproductive disease was also significantly associated with infertility (OR = 8.33; 95% CI: 2.60–26.72; p < 0.001), while risky environmental exposure increased the odds of infertility by 4.24 times (95% CI: 1.41–12.70; p = 0.007). These findings indicate that infertility is associated with multiple behavioral, reproductive, and environmental factors. Implications: Reproductive health services should adopt a couple-centered approach that includes smoking cessation, reduction of alcohol consumption, early detection and management of reproductive disorders, and minimization of hazardous environmental exposure. The findings may support the development of preventive programs, reproductive health education, and early screening strategies for couples of reproductive age. Originality: This study provides an integrated assessment of behavioral, reproductive, and environmental factors associated with infertility at the couple level. Unlike studies that examine female or male factors separately, this research emphasizes infertility as a shared reproductive health condition requiring the involvement of both partners. However, multivariable analysis is still required to identify the factors independently associated with infertility.